A study of five types of Chinese syntactic errors committed by malay students and the pedagogical implications - Lau Su Kia; Lee Hui Ling; Ang Lay Hoon; Ng Lee Luan (2011)
All the public universities in Malaysia offer Chinese language classes for non-Chinese students to learn Chinese. The Malay undergraduates who enrolled in such Chinese language classes often face difficulties in learning the word order such as the use of “bei”, “ba”, “bi” as well as in constructing sentences which involve the use of double verbs and double objective nouns. This phenomenon reflects the learning difficulties that relate to inter-language influences. The focus of this study is on the problems faced by these students in learning the afore-mentioned syntactical elements. The respondents of the study consisted of 40 Malay undergraduate students who were enrolled in the Chinese classes at two public universities in Malaysia, i.e. University of Malaya (UM) and University Malaysia Kelantan (UMK). The mother tongue of these students is Malay and they have no background knowledge of Chinese to start with. These students only started learning Chinese upon enrolment into the two universities. The data is mainly collected from the students’ end-of-semester examination answer scripts, quizzes, take home exercises, and various in-class written exercises. The data was analyzed in accordance with the features of errors committed by the students in relation to the 5 pre-identified types of syntactic errors. In addition, the researchers also conducted interviews with Chinese language teachers/lecturers who teach Chinese as a second language in the two pre-mentioned universities. The focus of the interview sessions is to find out how these instructors plan and teach the various syntactic structures in their classes. The outcome of the interviews were then analyzed qualitatively. The findings of the study revealed that the main factor that causes the Malay students to commit such syntactic errors is due to negative transfer interferences, i.e. the influence of their mother tongue (Malay).